Assessing customer satisfaction: the case of test prescribers at the clinical biology laboratory of Centre Muraz/ Institut National de Santé Publique, Burkina Faso - Dame Yenyetou; Issouf Sanou; Chérileila Thiombiano; Bakary Diamoutany Sogodogo; Adama Sanou; Soufiane D. Sanou; Mamoudou Cisse; Amariane M. M. Kone; Aline R. Ouoba; Dramane Kania; Michel K. Gomgnimbou; Ibrahim Sangare; et al. (BMC Health Services Research)
Abstract Context Assessing customer satisfaction with a product or service is one technique for evaluating the quality of a product or service given by a company. One of the instruments used to gauge customer satisfaction is the satisfaction survey. The Clinical Biology Laboratory of Centre Muraz employed this method to determine how satisfied its test prescribers were to improve. Method This was a cross-sectional study that took place in Bobo-Dioulasso from November 18 to December 26, 2022. Following a literature review, a questionnaire of twenty-three (23) questions was created. The questionnaire was distributed to the laboratory's prescribers, who were contacted ahead of time and consented. KoboToolbox, a data collection platform, was used. To compute frequencies, Microsoft Excel 2016 was utilized. A multivariate logistic regression model was run using R statistical software to identify the variables that best explained overall satisfaction. Results Participants came from 19 different health care facilities. 82 prescribers completed the satisfaction survey. Overall satisfaction was 56.03%. It was 65% for nurses and 47.12% for physicians. According to the regression model, the variables "communication with the laboratory," "interpretation of test results," and "delay in reporting results" substantially explained overall satisfaction, with p values of 0.04562, 0.03674, and 0.00987, respectively. Conclusion The overall satisfaction rate among the prescribers was relatively low. By acting on the significant variables, the laboratory will be able to improve this satisfaction.